PEMBANGUNAN KOTA PAGAR ALAM DAN PROSPEKNYA DI MASA DEPAN DITINJAU DARI ASPEK PENGELUARAN DANA PEMBANGUNAN - Fachrizal Bachri (Department of Development Economics, Universitas Sriwijaya, 2010)
The study focused on discussion of current Pagar Alam city local finance in regional development and its relation to the future prospect including the constraints and limitations faced in terms of budget allocation and execution of development. The study also discussed the relation between the ability of its local finance in regional development and its relation to the formation of a new regency (Tanah Besemah regency) which includes City of Pagar Alam. Assuming the security and political environments are conducive and spacious area is not increased so the prospects of PAD revenues in the future tends to increase. Thus the expected development in Pagar Alam will be better and move forward. In line with the expectation, the economy of Pagar alam will get better performance and the employment opportunities will be widened, and finally the people's welfare will also increase. Further efforts expected by the City of Pagar Alam government are to increase communities prosperity programs through increasing local finance revenues which is owned as well as through regional and global competition. Keywords: Regional Revenue, Fiscal Policy